Guarantee of services to citizens: A case study of Karnataka - Rajneesh, Shalini (2013)
The process of service delivery is at the heart of several governance issues. The experience world over has shown that an enabling environment, a willing political leadership and civil service are a pre-requisite to attain an optimum level of public service delivery. A number of factors contribute to an efficient service delivery among which governance remains to be of paramount significance. Various instruments of governance, including an acknowledgement of citizens' entitlements to put power in the hands of users of services and transforming accountability of services through realtime supervision have been identified as key to service delivery reforms. A number of Indian states have enacted legislation to guarantee well-timed delivery of public services as a matter of citizens' rights. These laws also provide for the imposition of a penalty on the bureaucrats who fail to deliver services within the particular time frame. The article elucidates the central features and implementation set-up of the Guarantee of Services to Citizen initiative of the Government of Karnataka
Keywords: Public utilities - India - Karnataka; Public utilities